enGendered : God's gift of gender difference in relationship - Andreades, Sam A., 1962- (Wooster, Ohio : Weaver Book Company, 2015)
"A systematic biblical theology of gender that affirms gender equality without minimizing the asymmetry of gender distinction based in the image of the triune God. Consequently, intergendered relationships, celebrating distinction across the genders, foster greater intimacy than monogendered (same-sex) or egalitarian ones"--
Includes bibliographical references and index.
Keywords: Man-woman relationships -- Religious aspects -- Christianity; Sex role -- Religious aspects -- Christianity; Intimacy (Psychology) -- Religious aspects -- Christianity; Homosexuality -- Religious aspects -- Christianity; Homosexuality -- Religious aspects -- Christianity; Intimacy (Psychology) -- Religious aspects -- Christianity; Man-woman relationships -- Religious aspects -- Christianity; Sex role -- Religious aspects -- Christianity